Non-hormone replacement therapy to overcome premature ovarian insufficiency: advances in natural products and stem cells targeting autophagy - Yang, Xinxin; Jia, Zhicheng; Shi, Mengyu; Li, Yongqian; Zhang, Guangheng; Wang, Peixuan; Sun, Xinwei; Qi, Wenlong; Guo, Ying (Frontiers in Endocrinology, 2025)
Premature ovarian insufficiency (POI) is the most common cause of female infertility. With the increase in people’s bad life habits, the causative factors of POI have increased, and its incidence has shown a rising trend year by year. At present, the commonly used clinical treatment for POI is hormonal replacement therapy (HRT), but it is not universally applicable and is prone to cause subsequent complications, posing certain health risks to patients with POI. Therefore, exploring greener, safer, and more efficacious non-hormonal treatments can help to address the clinical challenges of POI-induced infertility better. Studies have shown that autophagy plays a key role in the development and degeneration of oocytes from their origin to the follicle and that any alteration in autophagy affects the ovarian reserve in the follicle. Moreover, certain natural products and human stem cells from different sources can treat POI by modulating the autophagic pathway and have shown good efficacy. Therefore, our study aimed to review and analyze the previous research-based literature on natural product and stem cell therapy based on the autophagy mechanism of POI, and provide new insights and references for related scholars to continue to explore the autophagy mechanism of POI and non-hormone-targeted therapeutic strategies in depth.